New Aspects of EPR: Extending producer responsibility to additional product groups and challenges throughout the product lifecycle - Brown, Andrew (OECD Environment Working Papers, 2023)
Extended Producer Responsibility (EPR) is a policy approach that makes producers responsible for their products at the post-consumer stage of the lifecycle. It has been widely adopted by governments and companies across the OECD membership and beyond and is currently most commonly used for electronics, packaging, vehicles, and tyres. The success of EPR in increasing material recovery rates has triggered a debate about expanding the use of EPR to additional product groups. Additionally, there is a debate about expanding producer responsibilities to additional impact categories, which go beyond the traditional use of EPR to cover end-of-life costs that occur at the domestic level. This paper presents a discussion of relatively novel applications of EPR to additional product groups (plastic products beyond packaging, textiles, construction materials, and food waste) and to environmental impacts (design considerations, pollution and littering) that occur throughout the product lifecycle. Based on select case studies, this report evaluates the successes and challenges that early adopters of applying the EPR approach to new product groups or additional environmental impact categories have experienced. It reviews the arguments for further application of EPR, possible limitations and provides guidance on when and how to best apply an EPR.